Hubungan Kualitas Jasa Pelayanan Perawat dengan Kepuasan Pasien di RSUD Dr. A Dadi Tjokrodipo Bandar Lampung Tahun 2023 - Liza Ayu Pratiwi; Dessy Hermawan; M. Ricko Gunawan (Malahayati Nursing Journal, 2023)
ABSTRACT Patient satisfaction is an important indicator that must be considered in health services. Patient satisfaction also depends on the quality or quality of nursing services. Measuring the level of patient satisfaction is closely related to the quality of nursing services. The cause of patient dissatisfaction is influenced by many factors, including those related to product and service quality, price, emotional, performance, aesthetics, population characteristics, service, location, facilities, communication, atmosphere, visual design. The results of free interviews with the head nurse in room E4 to find out nurse service satisfaction in 2022 showed that 60% of patients stated they were satisfied with the services provided by nurses. While 40% of patients were not satisfied with the services provided by nurses. To determine the relationship between the quality of nursing services and patient satisfaction at RSUD Dr. A Dadi Tjokrodipo Bandar Lampung. This type of research uses quantitative, the research design uses an analytical survey, with a cross sectional approach. The population in this study were patients who were hospitalized at RSUD DR. A. Dadi Tjokrodipo. The sampling technique uses purposive sampling. Univariate and bivariate data analysis using the chi square test. This research was conducted in July 2023. Most of the respondents stated that the quality of nurse services was in the unfavorable category, as many as 92 respondents (51.7%). Most of the respondents stated that patient satisfaction was in the unfavorable category of 100 respondents (56.2%). There is a relationship between the quality of nurse services and patient satisfaction at RSUD Dr. A Dadi Tjokrodipo Bandar Lampung in 2023. as input material to improve the quality of nursing services in providing better services for patients, by means of nurses showing readiness when providing nursing services. Keywords: Quality of Nurse Service, Satisfaction, Satisfaction  ABSTRAK Kepuasan pasien merupakan salah satu indikator penting yang harus diperhatikan dalam pelayanan kesehatan. Kepuasan pasien juga tergantung pada mutu atau kualitas pelayanan keperawatan. Pengukuran tingkat kepuasan pasien erat hubungannya dengan kualitas pelayanan keperawatan. Penyebab terjadinya ketidakpuasan pasien dipengaruhi oleh banyak faktor antara lain yang berhubungan dengan kualitas produk dan jasa, harga, emosional, kinerja, estetika, karakteristik penduduk, pelayanan, lokasi, fasilitas, komunikasi, suasana, desain visual. Hasil wawancara bebas kepada kepala perawat ruang E4 untuk mengetahui kepuasan pelayanan perawat pada tahun 2022, didapat hasil sebanyak 60% pasien menyatakan puas dengan pelayanan yang diberikan oleh perawat. Sedangkan 40% pasien tidak merasa puas dengan pelayanan yang diberikan perawat. Untuk mengetahui hubungan kualitas jasa pelayanan perawat dengan kepuasan pasien di RSUD Dr. A Dadi Tjokrodipo Bandar Lampung. Jenis penelitian menggunakan kuantitatif, rancangan penelitian menggunakan survey analitik, dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah pasien yang melakukan rawat inap di RSUD DR. A. Dadi Tjokrodipo. Teknik sampling menggunakan purposive sampling. Analisa data univariat dan bivariat menggunakan uji chi square. Penelitian ini dilakukan pada bulan Juli Tahun 2023. Sebagian besar responden menyatakan kualitas pelayanan perawat dengan kategori kurang baik sebanyak 92 responden (51,7%). Sebagian besar responden menyatakan kepuasan pasien dengan kategori kurang baik sebanyak 100 responden (56,2%). Ada hubungan kualitas jasa pelayanan perawat dengan kepuasan pasien di RSUD Dr. A Dadi Tjokrodipo Bandar Lampung Tahun 2023. sebagai bahan masukan untuk meningkatkan kualitas pelayanan keperawatan dalam memberikan pelayanan yang lebih baik bagi pasien, dengan cara perawat menunjukan kesiapan ketika melakukan pelayanan keperawatan. Kata Kunci: Kualitas Pelayanan Perawat, Kepuasan, Kepuasan